Pengetahuan dan persepsi masyarakat terhadap perilaku kepatuhan pencegahan Covid-19 - Eka Sutrisna; Mulyadi Mulyadi (Holistik Jurnal Kesehatan, 2022)
Background : Coronavirus Disease 2019 (Covid-19) is a new type of disease that has never been previously identified in humans. The virus that causes Covid-19 is called Sars-CoV-2. Common signs and symptoms of Covid-19 infection are symptoms of acute respiratory distress such as fever, cough, shortness of breath, and some cases have difficulty breathing, and X-rays show extensive pneumonia infiltrates in both lungs. The incubation period is on average 5-6 days and the longest incubation period is 14 days. Three (3) key messages for preventing COVID-19, namely maintaining distance, wearing masks and washing hands with soap, must continue to be carried out in order to break the chain of transmission of Covid-19 and all of them require community participation. Public awareness is the main key in breaking the chain of transmission and the spread of the COVID-19 disease.Purpose: Knowing the influence of public knowledge and perception on the behavior of Covid-19 prevention compliance.Method: The research was conducted by distributing questionnaires. This type of analytical research with a cross-sectional study design. The population of this study is the entire community in Cot Girek Village, totaling 900 people. The sample in this study amounted to 276 respondents who were selected using purposive sampling. The analysis used is univariate and bivariate. The statistical test used is the Chi Square test.Results: The results of the analysis of the total research scores of respondents' knowledge are included in the good category, perception in the negative category and compliance behavior obtained results that some respondents were obedient, with p = 0.000 < = 0.05 indicating that there was a significant influence of the knowledge variable on the Covid-19 prevention compliance behavior, and the risk that if knowledge is lacking, 4.132 X patients will become disobedient in preventing Covid-19 and p = 0.001 < = 0.05 indicating that there is a significant effect of the perception variable on Covid-19 prevention compliance behavior, and the risk is that if the perception is negative, 2,253 X patients will become disobedient in preventing Covid-19.Conclusion: There is an influence between respondents' knowledge and perceptions of the Covid-19 prevention compliance behavior in Cot Girek Village, North Aceh Regency.Keywords: Knowledge; Perception; Society; Compliance; Prevention; Covid-19Pendahuluan: Coronavirus Disease 2019 (Covid-19) adalah penyakit jenis baru yang belum pernah teridentifikasi sebelumnya pada manusia. Virus penyebab Covid-19 ini dinamakan Sars-CoV-2. Tanda serta gejala umum infeksi Covid-19 yaitu gejala gangguan pernapasan akut seperti demam, batuk, sesak napas, dan beberapa kasus mengalami kesulitan bernapas, dan hasil rontgen menunjukkan infiltrat pneumonia luas di kedua paru. Masa inkubasinya rata-rata 5-6 hari dan masa inkubasi terpanjang yaitu 14 hari. Tiga (3) pesan kunci pencegahan COVID-19 yaitu jaga jarak, pakai masker dan cuci tangan pakai sabun harus tetap dilakukan guna memutus mata rantai penularan covid-19 dan semuanya membutuhkan peran serta masyarakat.  Kesadaran masyarakat, merupakan kunci utama dalam melakukan pemutusan mata rantai penularan dan penyebaran penyakit covid-19. Tujuan: Mengetahui  pengaruh pengetahuan dan persepsi masyarakat terhadap perilaku kepatuhan pencegahan covid-19.Metode: Penelitian dilakukan dengan penyebaran kuisioner. Jenis penelitian analitik dengan desain study crossectional. Populasi penelitian ini adalah seluruh masyarakat di Desa Cot Girek yang berjumlah 900 orang. Sampel pada penelitian ini berjumlah 276 responden yang dipilih dengan menggunakan purposive sampling. Analisis yang digunakan adalah univariat dan bivariat. Uji statistik yang digunakan yakni uji Chi Square.Hasil: Hasil analisis dari total skor penelitian pengetahuan responden termasuk kedalam kategori baik, persepsi dalam kategori negatif dan perilaku kepatuhan diperoleh hasil sebagian responden patuh, dengan p = 0,000< α = 0,05 menunjukan terdapat pengaruh yang signifikan variabel pengetahuan terhadap perilaku kepatuhan pencegahan Covid-19, dan resiko bila pengetahuan kurang maka akan terjadi 4,132 X pasien menjadi tidak patuh dalam pencegahan Covid-19  dan p = 0,001< α = 0,05 menunjukan terdapat pengaruh yang signifikan variabel persepsi terhadap perilaku kepatuhan pencegahan Covid-19, dan resiko bila persepsi negatif maka akan terjadi 2,253 X pasien menjadi tidak patuh dalam pencegahan Covid-19.Simpulan: Terdapat pengaruh antara pengetahuan dan persepsi responden terhadap perilaku kepatuhan pencegahan Covid-19 di Desa Cot Girek Kabupaten Aceh Utara.